PERANCANGAN SISTEM INFORMASI SEKOLAH BERBASIS WEBSITE (STUDY KASUS SD NEGERI CISARUA) - Rizwan Nurfalah; Arny Lattu (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
Cisarua Elementary School is a public school institution under the auspices of the government which is engaged in education. Currently, Cisarua Elementary School still has the habit of conveying school information to the community using conventional methods. So that it becomes an obstacle for the community to get information, they have to go to the location of Cisarua Elementary School. In this study the authors created a website-based school information system service using the Extreme Programing method which aims to facilitate the provision of accurate and reliable information to the public. In developing a website-based school information system, there are several approaches or methods used, in this study the method used was Extreme programming to build a school website. Extreme programming is a software engineering process that tends to use an object-oriented approach and the goal of this method is teams that are formed on a small to medium scale and this method is also suitable if the team is faced with unclear requirements or changes in requirements occur. which is very fast. The results of this study are in the form of a website-based school information system that can make it easy for the public to obtain school-related information.